Motion picture output in digital commercial advertising: وسام عبد عبد العزيز -نعيم عباس حسن (Al-Academy, 2020)
Mobile advertising has become the product of an influential actor in the creation of design ideas that attract the recipient, according to the needs of the society and the interactions of the technological technical age, what the technologies of the mock programs do and what corresponds to the expectations of the recipient, and what the design methods achieve of synchronization and sound in which all The research has found ways to address the most exciting and important snapshots and focus on diversity and diversity, formality, image and color, and what the optical degrees and chromatography achieve sought to attract attention, which contributes from the point of view of the researchers in the field of accuracy, clarity, attention and contrast, has reached Research on the importance of the moving image and its rhetorical and symbolic potential in the significance and absorption, attention and focus on the inclusion of the vocabulary of the animated image advertising within the training and educational programs in the relevant institutions